Increased Interstitial Concentrations of Glutamate and Pyruvate in Vastus Lateralis of Women with Fibromyalgia Syndrome Are Normalized after an Exercise Intervention: a Case-Control Study - Gerdle, Björn; Ernberg, Malin; Mannerkorpi, Kaisa; Larsson, Britt; Kosek, Eva; Christidis, Nikolaos; Ghafouri, Bijar (Linköping University, 2016)
This study investigates the interstitial concentrations of algesics and metabolites in the vastus lateralis muscle of 29 women with FMS and 28 healthy women before and after an exercise intervention.

The dataset consists of two PDF files. One contains variables with corresponding explanation, the other contains the measured values.

The dataset was originally published in DiVA and moved to SND in 2024.

Denna studie undersöker koncentrationerna av smärtframkallande ämnen och metaboliter i muskeln vastus lateralis hos 29 kvinnor med FMS och 28 friska kvinnor före och efter ett träningsprogram.

Datasetet består av två PDF-filer. Den ena innehåller variabler med tilllhörande förklaring, den andra innehåller de uppmätta värdena.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Increased Interstitial Concentrations of Glutamate and Pyruvate in Vastus Lateralis of Women with Fibromyalgia Syndrome Are Normalized after an Exercise Intervention: a Case-Control Study
Keywords: public health medicine; folkhälsovetenskap; clinical medicine; klinisk medicin; Clinical Medicine; Klinisk medicin; Nursing; Omvårdnad; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin